Assessment Practices at University Level: A Case Study of Abdul Wali Khan University Mardan - Ali, Iftikhar; Dr Saqib Shehzad; Dr Samreen Mehmood, (Dialogue Social Science Review (DSSR), 2024)
The study was design to explore the assessment practices at university level. Objectives of the study were to explore the assessment practices at university level, to inquire the rubric assessment practices at university level and to investigate the effectiveness of assessment practices in enhancing students higher order thinking skills at university level. The study was qualitative. All of the teachers (450) and students (16500) from the Abdul Wali Khan University Mardan make up the study's population. Ten professors (five from the scientific department and five from the arts department) and ten students (five from the science department and five from the arts department) made up the research people, which was sampled with purpose. The method for gathering data was a semi-structured interview guide that the researcher had created on his own. Thematic analysis was used to analyse the data that had been gathered. Based on findings it was concluded that Majority of the respondents (students) stated that there is no actual interview and practice of diagnosing students learning difficulties. All the respondents stated that learning progress are assessed through assignment, asking questions during and after class, quizzes, presentations, attendance, open book assignments, homework, and tests. Most of the respondents elaborated that at Abdul Wali Khan University Mardan the papers for semester/annual system are constructed through conventional approach.